Addressing integrity in the workplace: Strategies for promoting ethical behavior among employees - Ismail, Fadillah; Anthony , Deaverlyne (Journal of Islamic, Social, Economics and Development, 2025)
Integrity in the workplace plays a pivotal role in maintaining organizational success and fostering ethical behavior among employees. This study investigates the challenges organizations face in promoting integrity and the strategies that can be implemented to enhance ethical practices. The problem lies in the prevalence of unethical behaviors such as fraud, harassment, and corruption that continue to undermine organizational values. The objective of this research is to identify effective methods for promoting ethical behavior, with a focus on leadership, training, and organizational policies. The study utilizes a mixed-methods approach, combining qualitative insights from employee experiences with quantitative assessments of ethical outcomes. The results suggest that ethical leadership, structured training programs, and robust policies are critical in mitigating unethical behaviors and improving organizational culture. The implications of this research emphasize the importance of fostering a culture of integrity, which not only ensures long-term sustainability but also strengthens trust with stakeholders and enhances overall employee morale.